MINAT BELAJAR SISWA TUNAGRAHITA RINGAN PADA PEMBELAJARAN SENI RUPA DI SLSB FAN REDHA PADANG - DEDTA WULANDARI, Drs. Ajusril S., Drs. Eswendi, M.Pd. (Universitas Negeri Padang, 2016)
Learning activities SLB Fan Redha Padang art in the field seen students who often chide, and out of the classroom, less serious, do not carry supplies and not doing their jobs. In accordance with these problems, carried out research with the aim to describe mild mental retardation student in learning the art in the field SLB Fan Redha Padang. This research uses descriptive quantitative research methods. Based on research in the field of data processing, the results are as follows; 1) a sense of excitement in learning the art is very good (64.0%), 2) the student's interest in learning the art is very good (64.0%), 3) the students' attention on learning the art is very good (52.0%) , 4) the involvement of students in learning art is excellent 56.0% 5) teaching materials and teacher attitudes to learning art are in good and excellent (44.0%), 6) mild mental retardation student interest in learning the art SLB Fan Redha Padang is very good (52.0%). The conclusion in the research mild mental retardation student interest in learning the art in SLB Fan Redha Padang is very good.